(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study is to develop a STEAM education program for children using educational robots, and to analyze questions asked by children as a prior basic study. To this end, 29 children (16 boys and 13 girls) aged 3, 4 and 5 who had never experienced unplugged educational robots play were surveyed and observed, and 184 questions were extracted from video data containing a total of 300 minutes of play time. We divided the voluntary questions of children by age and analyzed them according to STEAM elements. T(Technology) was the most common STEAM element for all ages. Research results is meaningful in presenting the direction for convergent experiences and the development of computational thinking to meet the demand of the present childhood education to provide integrated education.